The Application of Second Language Acquisition Theories in Current English Teaching - Wang, Yingyu (Transactions on Social Science, Education and Humanities Research, 2024)
Nowadays, in the context of the globalization of English, whether it is for traveling abroad, studying, doing business or other circumstances, people can use English. Today as a universal language, the importance of English is self-evident. Many countries, especially those whose mother tongue is not English, are attaching greater importance to the teaching of English as a second language. This paper first presents and introduces the theories related to second language acquisition. Then it explores the phenomena existing in English teaching at the present stage including the inactivity of students in class, the irrationality of language input, the shortage of language acquisition environment and the emotional problems of students. Finally, it utilizes these theories to enlighten contemporary English teaching by putting forward some suggestions such as the development of a sense of purpose, the provision of effective input, the transition of teaching mode, the recruitment of foreign talents as well as the decrease of affective filtering, aiming at providing a reference for today's English teaching.